The glorious romantics [videorecording] a poetic return to the Regency - Jamson, Marshall; Perry, William ([Nebraska] Nebraskan ETV (Great Amwell Production [producer], 1993)
Selections from Byron, Keats and Shelley reveal the individuality and independence of spirit of England's Romantic poets. British actress Jean Marsh complements a wonderful ensemble of actors as this program delights in the words of romance.
Part One. Lord Byron (30 min.) -- Part Two. John Keats (30 min.) -- Part Three. Percy Bysshe Shelley (30 min.)
VHS.
Neil Hunt as Lord Byron; Stephen Lang as Percy Bysshe Shelley; Nicholas Woodeson as John Keats.
Keywords: Byron, George Gordon Noel Byron -- Baron, 1788-1824.; Keats, John Bertrand -- 1936-.; Shelley, Percy Bysshe; English poetry -- England